2016
DOI: 10.1002/cncr.29991
|View full text |Cite
|
Sign up to set email alerts
|

Role of isolated limb perfusion with recombinant human tumor necrosis factor α and melphalan in locally advanced extremity soft tissue sarcoma

Abstract: Isolated limb perfusion with recombinant human tumor necrosis factor α and melphalan (TNF-ILP) is a highly effective regional treatment for locally advanced soft tissue sarcoma. This review critically discusses the indication for TNF-ILP. AbstractManagement of locally advanced extremity soft tissue sarcoma of the limbs is challenging particularly in recurrent tumors and those adjacent to neurovascular bundles and joints. Typically the tumors are large, below the fascia and of high grade (T2b, stage III accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…When comparing the pathological tumor response with other published data, HCT achieved a (nearly) complete response rate of 45.2%, defined as less than 10% vital tumor cells after neoadjuvant treatment. This rate compares favorable to more invasive treatment approaches like isolated limb perfusion with tumor necrosis factor a and melphalan with nearly complete response rates between 17 and 47% [44]. Histopathological treatment results after HCT or CRT in our study are comparable to studies investigating CRT: Kraybill et al [18] reported a rate of 27% complete pathological response, DeLaney et al [45] reported a complete response rate of only 8% (4 of 48 patients).…”
Section: Discussionsupporting
confidence: 73%
“…When comparing the pathological tumor response with other published data, HCT achieved a (nearly) complete response rate of 45.2%, defined as less than 10% vital tumor cells after neoadjuvant treatment. This rate compares favorable to more invasive treatment approaches like isolated limb perfusion with tumor necrosis factor a and melphalan with nearly complete response rates between 17 and 47% [44]. Histopathological treatment results after HCT or CRT in our study are comparable to studies investigating CRT: Kraybill et al [18] reported a rate of 27% complete pathological response, DeLaney et al [45] reported a complete response rate of only 8% (4 of 48 patients).…”
Section: Discussionsupporting
confidence: 73%
“…In this context, TNF is a pleiotropic cytokine that promotes immune surveillance and directly kills cancer cells (5). Despite the promise of TNF as an anti-tumor agent, systemic TNF-induced toxicity precluded clinical development of this cytokine, other than in the setting of isolated limb perfusion for sarcomas (8). Noteworthy, however, are the findings that intratumoral administration of TNFerade has activity in the treatment of diverse human cancers (10), supporting the premise that a system for the delivery of TNF to tumors, while circumventing the systemic toxicity, could be an effective anti-cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We and others investigated the effectiveness of recombinant human TNF as a clinical anti-cancer agent; however, systemic side effects, such as fever, fatigue and hypotension, precluded its further development (6, 7). As a way of ameliorating the systemic toxicities, TNF has been approved in Europe for administration by isolated limb perfusion in the treatment of patients with locally advanced extremity soft tissue sarcoma (8). Another approach for the clinical development of TNF involved intratumoral delivery of an adenoviral vector encoding TNF under the control of a radio- and chemo-inducible promoter (TNFerade) (9).…”
Section: Introductionmentioning
confidence: 99%
“…vascular leak syndrome, nausea and fever) are frequently observed [13][14][15]. Recombinant TNF (Beromun ® ) has been approved for the treatment of soft-tissue sarcoma patients only for isolated limb perfusion procedures [16][17][18][19], whereas recombinant interferons have received marketing authorization for the treatment of various types of malignancies [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This feature, which may initially appear as paradoxical, is easy to understand considering the fact that only a small amount of product (in absolute terms) reaches the tumor mass (approximately 5-20 percent injected dose per gram in mice and 0.01-0.1 percent injected dose per gram in patient) [39,40]. Exposure of blood and normal organs to pro-inflammatory cytokines may cause hypotension, flu-like symptoms, nausea and vomiting [13][14][15][16][17][18][19][20][21]. Intense research activities are devoted to the search for methods which preserve the therapeutic activity of engineered cytokine products, while decreasing systemic toxicity [24].…”
Section: Introductionmentioning
confidence: 99%